"By faith alone" (undivided loyalty) in light of change agency theory: Jesus, Paul and the Jesus-group in Colossae - Aarde, Andries van (HTS teologiese studies, 2017)
This article aims to apply the model of change agent to the interpretation of Colossians. Presuming a continuity between Jesus and Paul, the article introduces the concept of ‘by faith alone’ from the Pauline letters. By this expression is meant an undivided fidelity to an inclusive approach to understanding God’s work, with concrete historical roots in Jesus’ crossing of gender, ethnic and cultural boundaries. Living in this manner requires reformation, transformation and change. The study spells out in fuller detail what is understood ‘by faith alone’ by discussing the meaning of ‘faith’ within its semantic domain embedded in the codes of 1st-century Mediterranean culture. Living in faith is both a change of one’s inner convictions and about a life in faith.